STEM-26. SMALL MOLECULE DRUG CBL0137 INHIBITS THE FACT COMPLEX AND SENSITIZES GLIOBLASTOMA CANCER STEM CELLS TO RADIOTHERAPY. (9th November 2020) - Tallman, Miranda; Zalenski, Abigail; Deighen, Amanda; Schrock, Morgan; Mortach, Sherry; Grubb, Treg; Kastury, Preetham; Huntoon, Kristin; Summers, Matthew; Venere, Monica
Abstract: Glioblastoma (GBM) is a malignant brain tumor with nearly universal recurrence. GBM cancer stem cells (CSCs), a subpopulation of radio- and chemo-resistant cancer cells capable of self-renewal, contribute to the high rate of recurrence. The anti-cancer agent, CBL0137, inhibits the FACT (facilitates chromatin transcription) complex leading to cancer cell specific cytotoxicity. Here, we show that CBL0137 sensitized GBM CSCs to radiotherapy using both in vitro and in vivo models. Treatment of CBL0137 combined with radiotherapy led to increased DNA damage in GBM patient specimens and failure to resolve the damage led to decreased cell viability. Using clonogenic assays, we confirmed that CBL0137 radiosensitized the CSCs. To validate that combination therapy impacted CSCs, we used an in vivo subcutaneous model and showed a decrease in the frequency of cancer stem cells present in tumors as well as decreased tumor volume. Using an orthotopic model of GBM, we confirmed that treatment with CBL0137 followed by radiotherapy led to significantly increased survival compared to either treatment alone. Radiotherapy remains a critical component of patient care for GBM, even though there exists a resistant subpopulation. Radio-sensitizing agents, including CBL0137, pose an exciting treatment paradigm to increase the efficacy of irradiation, especially by inclusively targeting CSCs.